The Effect of Giving a Combination of Lavender Aromatherapy Oil and Oxytocin Massage on the Smooth Flow of Breast Milk in Breastfeeding Mothers - Yasiroh, Umi; Wardani, Endah Kusuma; Soekardjo, Soekardjo (Placentum: Jurnal Ilmiah Kesehatan dan Aplikasinya, 2024)
Introduction: Breast milk is known to have good nutritional content, following WHO recommendations regarding the importance of exclusive breastfeeding for babies during the first six months. The factors inhibiting the release of breast milk are very diverse, and one way to overcome this is by giving a combination of lavender aromatherapy oil and oxytocin massage by massaging the back area of the spine. Combining these two methods can influence the flow of breast milk to increase the release of the hormone oxytocin. The research aimed to identify the effect of a combination of lavender aromatherapy oil and oxytocin massage on the smooth flow of breast milk in breastfeeding mothers.Methods: This type of research is pre-experimental with a one-group pretest-posttest design approach. The number of respondents was 30 breastfeeding mothers using the accidental sampling research method according to the inclusion and exclusion criteria. The independent variable combines lavender aromatherapy oil and oxytocin massage, given three times a week according to the SOP for 15-20 minutes for each respondent. The dependent variable is smooth breastfeeding, conducting interviews and observations before and after the intervention. Data analysis used the Wilcoxon test.Result: The research results before the intervention were that half of the respondents had good breastfeeding fluency, namely 15 people (50%), and after being given the intervention, most respondents had good breastfeeding fluency, namely 20 people (66.7%). The Wilcoxon test results showed a p value of 0.000, which means that there is an effect of giving a combination of lavender aromatherapy oil and oxytocin massage on the smooth flow of breast milk in breastfeeding mothers.Conclusion: It is hoped that the results of this research can be applied to support exclusive breastfeeding and used as a source of information, reference, and comparison in handling breast milk disorders in breastfeeding mothers for further research